Sistem Informasi Pembelian dan Penjualan Pupuk Disertai dengan Perhitungan Harga Pokok Produksi yang Dilengkapi Tracking Pengiriman - Stevanoes, Alvian; Rizky Wicaksono, Soetam (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
This study was conducted with the aim of designing and developing an information system for fertilizer distribution at PT. Subur Tani Utama. The system includes the recording of raw material purchases, inventory management, product repackaging processes, distribution to client factories, delivery tracking based on geolocation, and payment recording. The development method employed was the Waterfall model, consisting of requirements analysis, system design, implementation, and testing. The application was designed as a web-based system using PHP programming language and MySQL database, supported by a responsive user interface. The implementation results indicate that the system can generate integrated reports on inventory, distribution, repackaging costs, and payments. Therefore, the designed system supports the company’s internal operations by enabling more structured documentation and providing more accurate information for fertilizer distribution management.